2020
DOI: 10.1098/rspb.2020.2454
|View full text |Cite
|
Sign up to set email alerts
|

Infectious disease and sickness behaviour: tumour progression affects interaction patterns and social network structure in wild Tasmanian devils

Abstract: Infectious diseases, including transmissible cancers, can have a broad range of impacts on host behaviour, particularly in the latter stages of disease progression. However, the difficulty of early diagnoses makes the study of behavioural influences of disease in wild animals a challenging task. Tasmanian devils ( Sarcophilus harrisii ) are affected by a transmissible cancer, devil facial tumour disease (DFTD), in which tumours are externally visible as they progress. Using telemetry an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 53 publications
1
26
0
1
Order By: Relevance
“…As DFTD tumors grow, they can grossly disrupt the structure of the mouth and jaw, causing necrosis, ulcerations, and secondary infections (Figure 1) (Loh et al., 2006; Pye, Hamede, et al., 2016; Pye, et al., 2016), potentially resulting in a competitive disadvantage for some infected individuals during feeding interactions. Given that devils reduce their social contacts in response to DFTD infection both inside and outside of the mating season (Hamilton et al., 2020), an alteration in diet may facilitate reduced competition and avoidance of conspecific aggression, or be the result of ostracization of diseased individuals by healthy conspecifics. Devils may switch to a diet that can be consumed relatively quickly, easily, and solitarily, carrying a lower risk of costly competition.…”
Section: Introductionmentioning
confidence: 99%
“…As DFTD tumors grow, they can grossly disrupt the structure of the mouth and jaw, causing necrosis, ulcerations, and secondary infections (Figure 1) (Loh et al., 2006; Pye, Hamede, et al., 2016; Pye, et al., 2016), potentially resulting in a competitive disadvantage for some infected individuals during feeding interactions. Given that devils reduce their social contacts in response to DFTD infection both inside and outside of the mating season (Hamilton et al., 2020), an alteration in diet may facilitate reduced competition and avoidance of conspecific aggression, or be the result of ostracization of diseased individuals by healthy conspecifics. Devils may switch to a diet that can be consumed relatively quickly, easily, and solitarily, carrying a lower risk of costly competition.…”
Section: Introductionmentioning
confidence: 99%
“…Having observed a positive association between social network and geohelminth infection, we then tested the impact of sampling bias on these results, by including/excluding certain age-sex classes from the analysis. For various reasons, numerous studies have focused on specific age-sex classes rather than the whole social group (Hamilton et al, 2020; Roberts and Roberts, 2020; Sandel et al, 2021; Webber et al, 2016). Through targeted removal of network subsets and subsequent reanalysis, we demonstrated that the original relationship observed using the whole group network becomes insignificant, both in classical statistical terms (i.e., loss of statistical significance) and in absolute quantitative terms, as the model parameter estimates were in some cases considerably lower, to the point where we could not conclude from randomisation tests that the observed effects of sociality on parasitism were different from those expected to arise by chance.…”
Section: Discussionmentioning
confidence: 99%
“…Having observed a positive association between the social network and geohelminth infection, we then tested the impact of sampling bias on these results, by including/excluding certain age-sex classes from the analysis. Numerous studies have focused on specific age-sex classes rather than the whole social group (Hamilton et al, 2020;Roberts and Roberts, 2020;Sandel et al, 2021;Webber et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Es un tumor contagioso que se "aloinjerta" en piel de la cara de estos ejemplares y puede causar su muerte en un plazo de seis meses (Figura 5). La transmisión ocurre por medio de la inoculación de las células a partir de mordeduras que se generan durante el apareamiento los demonios de Tasmania o durante la competencia de alimento entre individuos (McAloose & Newton, 2009;Hamilton et al, 2020;Welsh, 2011). A diferencia de otros tipos de cáncer, el tumor venéreo transmisible de los perros puede atenderse con aplicación de quimioterapia, incluso hay reportes de regresión espontánea del tumor; sin embargo, en el caso de los tumores faciales de los demonios de Tasmania por lo general son fatales (Hamilton et al, 2020;Welsh, 2011).…”
Section: Cáncer "Heredado"unclassified